Mechanism of legal regulation of transportation - Шишка, Роман Богданович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article refers to the legal mechanism for regulating relations with transportation as areas of legal enforcement of the law in a legally meaningful behavior of the participants. Pay attention not shortcomings of current legislation and regulations proposed to those that are contrary to the Constitution of Ukraine and the Central Committee of the Civil Code of Ukraine abolished. The attention on the elements of the legal regulation of relations that are modeled by the law and on the ratio of contractual and legal regulation.